2002
DOI: 10.1177/026119290203000104
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Study of the Toxicity of Mercury Dichloride and Methylmercury, Assayed by the Frog Embryo Teratogenesis Assay-Xenopus (FETAX)

Abstract: The Frog Embryo Teratogenesis Assay-Xenopus (FETAX) is a powerful and flexible bioassay that makes use of the embryos of the anuran amphibian Xenopus laevis. The FETAX can detect xenobiotics that affect embryonic development, when mortality, teratogenicity and growth inhibition are used as endpoints. The FETAX was used to compare the embryotoxic and teratogenic potentials of two chemical species of mercury: inorganic mercury(II) chloride (HgCl2) and organic methylmercury chloride (MeHgCl). MeHgCl, with an esti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
26
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 37 publications
2
26
0
Order By: Relevance
“…2a). This agrees with the TC 50 and LC 50 (~50 μg/l and ~70 μg/l) calculated from previous work in X. laevis at unknown density for 120 hours (approximately stage 47) (Prati et al 2002), and the LC 50 (~100-125 μg/l) observed in zebrafish at more similar developmental time points (Hassan et al 2012; Ho et al 2013 Supplementary Fig. 5).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…2a). This agrees with the TC 50 and LC 50 (~50 μg/l and ~70 μg/l) calculated from previous work in X. laevis at unknown density for 120 hours (approximately stage 47) (Prati et al 2002), and the LC 50 (~100-125 μg/l) observed in zebrafish at more similar developmental time points (Hassan et al 2012; Ho et al 2013 Supplementary Fig. 5).…”
Section: Discussionsupporting
confidence: 91%
“…In vivo invertebrate studies with physiologically relevant exposures have shown a link between MeHg induced activation of the Notch pathway and a failure in proper neuron migration, survival, and axon outgrowth during Drosophila development (Engel et al 2012, 2014; Rand et al 2008, 2009). Embryological work using Xenopus at environmentally relevant concentrations of MeHg in solution found general toxicity beginning around 50 μg/l along with significant axial deformities and shortening of the embryo (Prati et al 2002), disruption of metamorphosis independent of T3 levels (Davidson et al 2011), and identified biomarkers strongly related to MeHg exposure (Monetti et al 2002). In rodents, many experiments involving human-like prenatal modes of exposure have examined the resulting behavioral and cognitive defects (for review see: Bisen-Hersh et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Further investigations are required to determine whether the effect of Se co-exposure on whole embryo Hg levels is due to alterations in uptake, metabolism, or excretion. Uptake of Hg parallels increased uptake of Se in both embryos and fetuses [65, 66]. Data from Weber et al [19] suggest that, while interactions also may occur at lower SeMet:MeHg ratios, it may not be sufficient to reduce behavioral alterations if both are present in the exposure media at higher concentrations.…”
Section: Discussionmentioning
confidence: 99%
“…Fresh water aquatic biota such as amphipods (Hyalella azteca) has been used to evauate contaminated sediments (Ingersoll et al 1998) in which survival growth and reproductive capacity are the main endpoints. African clawed frogs/FETAX (Xenopus laevis) (Prati et al 2002) were also used to assess mercury toxicity and applied evaluation of developmental early stages as an endpoint.…”
Section: Earthworms As Mercury Bioindicatorsmentioning
confidence: 99%